Enhancing Arabic Writing Skills Through the Genre-Based Approach in Senior High School - M Yahya Ashari; Mokhammad Miftakhul Huda; Rifatul Mahfudhoh (Postgraduate Study Programme of Universitas Islam Negeri KH. Achmad Siddiq Jember, Indonesia., 2024)
Arabic writing skills require systematic and progressive learning with clear stages like concept building, modeling, and practice. However, previous studies have often overlooked the importance of combining structured learning models with contextual themes in improving writing proficiency. Addressing this gap, the present study is going to investigate the application of the Genre-Based Approach using the Teaching Learning Cycles Model in Arabic writing instruction. The study is based upon the theme of Travel. The target population is 32 students. A qualitative approach with a descriptive method was used, whereby data were collected through classroom observation, assignments, tests, FGD, and documentation. Data were analyzed using descriptive analysis techniques. The results show that the GBA with the TLC Model provide gradual learning, through the introduction of concepts, modeling, and practice activities in group and individual settings. It also integrated the 4C skills of 21st-century learning: critical thinking, communication, collaboration, and creativity. Students' learning mastery increased from 39.72% to 87.19% with a mean increase from 60.28 to 81.67 after the intervention. The learning process was also rated positively by observers. This study concludes that GBA with the TLC Model is effective in improving Arabic writing skills through structured, contextual, and collaborative learning experiences.